The privatization of environmental health services: a national survey of practices and perspectives in local health departments. - Keane, Christopher (Association of Schools of Public Health, 2002)
OBJECTIVES: This article presents nationally representative data on environmental health (EH) services privatized by local public health departments, enforcement and assurance mechanisms for privatized services, and administrators' views about EH services that should not be privatized. METHODS: A national sample of 380 local public health departments, stratified by jurisdiction size, was drawn from a universe of 2,488 departments. Telephone interviews were conducted with 347 administrators of departments. Results were weighted to be nationally representative. RESULTS: Approximately one-quarter of departments had privatized at least one EH service, almost always to for-profit organizations. The two most common reasons given for privatizing EH services were cost savings or increased efficiency and lack of capacity or expertise to carry out the service. The most rigorous, although infrequent, technique of enforcement and assurance of EH standards when services were privatized was double-testing of samples. Departments more commonly relied on state licensing and certification of contractors. When asked what services should not be privatized, 27% of respondents cited EH services. Many respondents argued against privatizing environmental services that have inherent regulatory functions. They expressed concern that privatization would fragment the public health infrastructure by impairing communication, diminishing control over performance, or weakening health departments' capacity to respond to environmental and other health crises. CONCLUSION: These findings raise serious concerns about the privatization of EH.